Pengaruh Country/Region of Resident, Trip Characteristic, Tourism Preferences dan Personal Characteristics terhadap Sustainable Tourist Behavior - Antania Shinta Yuwono (EkoPreneur, 2020)
The background of this research study is to identify sustainable tourist behavior which is essential for enhancing sustainable tourism. The purpose of this study was (1) to Analyze the contribution and influence of Sustainable Tourist Behavior on Sustainable Tourism. (2) Analyze the factors that influence Sustainable Tourist Behavior. The design of this research applies quantitative study by spreading questioners to 125 tourists in Kuta, Bali. The data analysis used in this research was SEM by the support of the SPSS program and Amos program. The result of this study is that the Country/region of residents and personal characteristics not affect significantly sustainable tourist behavior. Trip characteristics, only first-time international tourist variable that affects tourist sustainable behavior. While for the tourism preferences that significantly influence sustainable tourist behavior are variable-length traveled to Kuta (duration) and the proportion of foreign travel for a year.  Keywords: tourists behavior, sustainable tourist behavior, sustainable tourism